Physical activity and vasomotor symptoms in perimenopausal women at Wukirsari Village, Yogyakarta, Indonesia - Iwi Liesdiyanata; Dicky Moch Rizal; Djaswadi Dasuki (DiscoverSys Inc., 2021)
Background: Menopause is an event that marks the end of the reproductive phase of a woman. Vasomotor symptoms are one of the primary symptoms of menopausal women and affect about 40-60% of perimenopausal women. This research aims to investigate the relationship of physical activity with vasomotor symptoms in perimenopausal women.Methods: The population in this study were 173 women aged 45-54 years who are still experiencing menstruation in the Wukirsari village working area of Puskesmas Cangkringan Sleman-Yogyakarta. The instrument for measuring vasomotor symptoms adopted two questions from the menopause rating scale (hot flushes and night sweats) questionnaire while measuring physical activity using a questionnaire from Riskesdas. Data were analyzed using SPSS version 23 for Windows.Results: Most of the participants were in the 45-50 years age group (75.73%), followed by severe vasomotor symptoms (95.95%), sufficient physical activity (91.91%), medium level education (49.71%), and informal occupation (94.80%). In addition, this study found that most of the participants were normal Body Mass Index (BMI) (54.34%), passive smoking (64.74%), and pre-hypertension (46.20%). There was a significant relationship between physical activities and BMI to the vasomotor symptoms among women of perimenopausal age (p<0.05).Conclusion: There was a significant relationship between physical activities and BMI the vasomotor symptoms among women of perimenopausal age.